HUBUNGAN PENDERITA DIABETES MELITUS TIPE 2 DENGAN DERAJAT COVID-19 DI RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG TAHUN 2020 - Resti Arinia; Naufal Hilmy Fathurochman; Tusy Triwahyuni; Mardheni Wulandari (Medula, 2022)
Covid-19 is a global public health problem and has a very fast transmission rate. In severe cases, it can cause acute respiratory syndrome, pneumonia and for the most severe cases it can cause death. Type 2 Diabetes Mellitus (DMT2)is a group of metabolic diseases. Characterized by hyperglycemia, it caused by abnormalities in insulin secretion. Decreased immunity for people with T2DM is one of the factors causing the occurrence of Covid-19. This research used observational analytic design with cross sectional method, using purposive sampling technique and ng Spearman Correlation test analysis. Most of the respondents experienced moderate Covid-19 degrees ( 138 people,54.1%) and 56 people with DMT2 were infected by Covid-19 (22%). There was a relationship between DMT2 and Covid-19 with a p-value obtained 0.003, which is a relationship between Type 2 Diabetes Mellitus and Covid-19.